Analysis on the valuation issues in the financial statements / Salim Hassan - Hassan, Salim (1988)
The title "Analysis on the valuation issues in the financial statements" has been chosen because this topic has not been widely discussed in Malaysia. Currently, the published financial statements have not been properly understood by most of their users particularly the general public (with the exception to other interested parties such as accountants, brokers, etc.) due to lack of accounting knowledge. Therefore, in this paper the discussion will be mainly on the methods of valuation of items in the financial statements with the hope that it may assist some users of accounts to gain a better understanding of the financial statements published.